Mapping Personality Types among EFL Learners: Insights from Indonesian University Students - Bay, Indri Wirahmi; Basalama, Nonny; Miolo, Sartin T.; Dako, Rahman Taufiqrianto (Randwick International of Education and Linguistics Science Journal, 2025)
This study aims to identify the personality types of students in the English Language Education Study Program (ELESP) at Universitas Negeri Gorontalo and to explore their pedagogical implications for English as a Foreign Language (EFL) learning. A quantitative descriptive design was employed, involving 118 undergraduate students from three academic cohorts (2021–2022, 2022-2023, 2023-2024). Data were collected through an adapted version of the Eysenck Personality Questionnaire (EPQ) developed by Eysenck and Eysenck (1975) and validated for Indonesian learners by Wulandari (2017). The instrument used a five-point Likert scale to measure extroversion and introversion tendencies. Descriptive statistics, including mean, standard deviation, frequency, and percentage, were computed using Microsoft Excel to determine personality distribution. The results revealed that most students (61.86%) were ambiverts, followed by extroverts (27.12%) and introverts (11.02%). These findings suggest that ELESP students tend to balance social engagement and reflective learning, offering advantages in diverse EFL classroom contexts. The study highlights the need for personality-responsive pedagogy that accommodates varied learner characteristics to promote more effective and inclusive language learning.